GC-MS and metabolomics analysis of amino acids, glucose and urinary metabolic pathways and characteristics in children with spleen-deficiency diarrhea - Xu, Shan; Wang, Shouchuan (Cellular and Molecular Biology, 2020)
Diarrhea is a disease, and patients must have bowel movements at least three times per day. This condition may last for several days and may cause dehydration due to fluid loss. Spleen-deficiency makes a person more vulnerable to some infectious diseases. Persistent diarrhea due to spleen-deficiency may affect amino acids and glucose metabolic pathways, and urinary metabolic characteristics. For this purpose, this research was carried out to investigate the pathogenesis and changes of metabolic profiling in urine samples that come from 3 months to 3 years old children with persistent diarrhea due to Spleen-deficiency were analyzed by metabolomics methods based on gas chromatography and mass spectrometry (GC-MS). The urine samples were collected and divided into normal children group (NC group, n=30), persistent diarrhea group (PD group, n=30)ï¼ŽThe endogenous metabolites in urine were obtained by GC-MS. Principal component analysis (PCA) and orthogonal partial least squares-discriminant analysis (OPLS-DA) was used to analyze the dataï¼ŽThe results were analyzed by one-way analysis of variance and Fold changeï¼ŽFinallyï¼Œthere was a significant difference between the normal group and the diarrhea group, and the significant metabolites, glutamic acid, serineï¼Œphenylalanine, histidine, and et al. were identified between two groups. The metabolism of glycine, serine and threonine, arginine and proline, glutathione and pentose phosphate were involved. The result demonstrated that amino acid metabolism and glucose metabolism were the main metabolic pathways and responsible for persistent diarrhea due to Spleen-deficiency.